2022
DOI: 10.3892/etm.2022.11126
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA TUG1 knockdown repressed the viability, migration and differentiation of osteoblasts by sponging miR‑214

Abstract: The maxillofacial region in the human body is susceptible to fracture and corresponding soft tissue injury. In the current study, the effect of long non-coding RNA (lncRNA) taurine upregulated gene 1 (TUG1) on maxillofacial fracture development was investigated. In total, 50 patients diagnosed with maxillary fracture and 50 healthy volunteers were enrolled in this study. Participants' TUG1 expression level in serum was measured using reverse transcription-quantitative (RT-q)PCR. After transfection with small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For instance, LncRNA TUG1 can adsorb miR-29c-3p, which enhances the malignant behavior of gastric adenocarcinoma [5]. Yao et al have found that knockout of LncRNA TUG1 can inhibit viability, CM, and differentiation and lead to CA of osteoblasts in patients with maxillary fractures, suggesting that LncRNA TUG1 is also involved in the biological process of osteoblast CP and CA [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, LncRNA TUG1 can adsorb miR-29c-3p, which enhances the malignant behavior of gastric adenocarcinoma [5]. Yao et al have found that knockout of LncRNA TUG1 can inhibit viability, CM, and differentiation and lead to CA of osteoblasts in patients with maxillary fractures, suggesting that LncRNA TUG1 is also involved in the biological process of osteoblast CP and CA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al reported that lncRNA TUG1 knockdown repressed the viability, migration, and differentiation of osteoblasts by sponging miR‐214. 25 A study by Zhang et al 26 demonstrated that silencing lncRNA TUG1 inhibits acute myeloid leukemia cell viability and promotes apoptosis by targeting the microRNA‐221‐3p/KIT axis. We performed functional analysis of TUG1‐plasmid or miR‐153‐3p mimic to explore whether lncRNA TUG1 mediated the functions of LPS in HRMCs and conducted a rescue experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have suggested that lncRNAs are involved in various biological processes, including cell proliferation, apoptosis, and invasion. Yao et al reported that lncRNA TUG1 knockdown repressed the viability, migration, and differentiation of osteoblasts by sponging miR‐214 25 . A study by Zhang et al 26 demonstrated that silencing lncRNA TUG1 inhibits acute myeloid leukemia cell viability and promotes apoptosis by targeting the microRNA‐221‐3p/KIT axis.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, they demonstrated that the lncRNA PVT1 acts as a miR-128-3p sponge and influences the regulation of the BMPs signaling pathway as well as the downstream signaling proteins BMP-2 and BMP-4 through the regulation of GREM1. More illustrative examples of the lncRNA/miRNA/mRNA axis functioning by activating BMPs signaling pathways are presented in Table 2 [ [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ].…”
Section: Lncrnas and Bmps Signaling Pathwaymentioning
confidence: 99%